Some proposals for the improvement of the methodics of the organization of championships - Stakvilevičius , M. (Psichologija, 1969)
We must look for new schemes of competitions to make championships of sports games help to increase sports progress of pupils maximally. We suggest a model of championship in which the result of each match has a character of probability. In such a case we have a linear system of algebraic equations r_k x_k-∑_(l=1)^(r_k)▒〖x_l=n_k 〗 (r_k – number of matches, x_k – a class, ∑_(l=1)^(r_k)▒x_l – the sum of the rival classes, n_k – a half of gained and lost balls) reflecting the competitions organized according to any scheme. In some cases the system of equations is solved analytically and the results are reduced to simple formulas. We suggest the following methods, illustrated by examples suggested for different championships. The suggested theory might be used by sportsmen and mathematicians in their work after classes.
Keywords: championships; competitions; methodics of the organization of championships